Reflections on leadership preparation research and current directions - Orr, Margaret Terry (Frontiers in Education, 2023)
This reflection addresses the need for research on how leadership preparation features develop candidates' leadership skills and practices, as aligned to recent research on how principals best influence student learning. It reviews the nature of leadership preparation research, the investments in preparation programs, how the field has promoted leadership preparation research, and new developments in related research. Guskey's program evaluation framework-which emphasizes evaluating the effects of professional learning on what candidates learn and do and the impact on their organizations-is useful in highlighting current shortcomings in how preparation features have been evaluated and identifying areas for further, more strategic research.